Simulating of the influence of fiscal regime adjustment on marginal oil field’s investment climate in Malaysia - Mas’ud, Abdulsalam; Abdul Manaf, Nor Aziah; Saad, Natrah (2015)
The need for improved governance of oil and gas sector and sustainability of production coupled with increasing number of stranded marginal oil fields mandated Malaysian authorities to adjust the fields’ fiscal regime.The new regime came with special incentives, and changed the fiscal arrangement from production sharing contract to risk service contract.The influence of the new regime in comparison to the old one on marginal oil fields’ investment climate was simulated under nine different scenarios relating to oil prices and reserves levels.Using internal rate of return, it was found that the fiscal regime under risk service contract has more favorable investment climate in majority of the scenarios- with exception to those relating to high oil prices, which fiscal regime under production sharing contract is more favorable.As implication for policy, to make the new fiscal regime more attractive under the risk service contract, contractors’ remuneration fee should be attached not only to performance but also to high oil price. In essence, incentives given to contractors should be higher during soared oil prices. Concern should be made for the assumptions employed while applying the results for a decision.